A novel two-stage approach for energy-efficient timetabling for an urban rail transit network - Huang, Kang; Liao, Feixiong (Transportation research. Part E, Logistics and transportation review, 2023)
•A general model framework of energy-efficient timetabling and passenger path choice in a URT network is proposed.•A novel model reformulation as a tree knapsack problem is developed to determine train running times by a pseudo-polynomial dynamic programming algorithm.•A heuristic sequencing method is developed to determine nonuniform headways and dwell times.•The relationship between optimal energy consumption reduction and travel time increment is explored. Urban rail transit (URT) is the backbone transport mode in metropolitan areas to accommodate large travel demands. The high energy consumption of URT becomes a hotspot problem due to the ever-increasing operation mileages and pressing agendas of carbon neutralization. The high model complexity and inconsistency in the objectives of minimizing passenger travel time and operational energy consumption are the main challenges for energy-efficient timetabling for a URT network with multiple interlinked lines. This study proposes a general model framework of timetabling and passenger path choice in a URT network to minimize energy consumption under passenger travel time constraints. To obtain satisfactory energy-efficient nonuniform timetables, we suggest a novel model reformulation as a tree knapsack problem to determine train running times by a pseudo-polynomial dynamic programming algorithm in the first stage. Furthermore, a heuristic sequencing method is developed to determine nonuniform headways and dwell times in the second stage. The suggested model framework and solution algorithm are tested using a real-world URT network, and the results show that energy consumption can be considerably reduced given certain travel time increments.